2014
DOI: 10.1088/1367-2630/16/10/103038
|View full text |Cite
|
Sign up to set email alerts
|

Streamer discharges can move perpendicularly to the electric field

Abstract: Streamer discharges are a primary mode of electric breakdown in thunderstorms and high voltage technology; they are generally believed to grow along electric field lines. However, we here give experimental and numerical evidence that streamers can propagate nearly perpendicularly to the background electric field. These streamers are guided by pre-ionization that is orders of magnitude lower than the ionization density in a streamer channel, hardly affecting the background field. Positive streamers could be gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
(33 reference statements)
2
47
0
Order By: Relevance
“…1, therefore, cannot reach the dielectric tip. A similar effect was observed in recent experiments [6]. There, it was shown that weak preionization, which does not influence the electric field, can guide positive streamers in nitrogen in directions perpendicular to the electric field lines.…”
supporting
confidence: 87%
“…1, therefore, cannot reach the dielectric tip. A similar effect was observed in recent experiments [6]. There, it was shown that weak preionization, which does not influence the electric field, can guide positive streamers in nitrogen in directions perpendicular to the electric field lines.…”
supporting
confidence: 87%
“…Second, we will change the pulse repetition frequency which influences density and distribution of the ion density remaining from the previous discharge. (We remark that the electron density remaining from the previous discharge should be negligible at these repetition frequencies in air [19].) 3.3.1.…”
Section: Effect Of Pressure and Pulse Frequencymentioning
confidence: 83%
“…But for a positive streamer to propagate with velocities comparable to electron drift against the electron drift direction, some electrons must be available in front of the streamer head. Their sources can be pre-ionization caused by natural ionization sources or by a laser [19], by leftover ionization of previous discharges, or by photoionizing radiation from the active ionization region of the streamer head [20][21][22].…”
Section: Discharge Developmentmentioning
confidence: 99%
“…The high voltage pulses create a streamer discharge in the vessel, which is imaged by an Andor ICCD-camera with stereoscopic optics between it and the vessel [12,13,26]. Like in [13], the angle between the two image paths is 24-28° and the orientation is such that streamers moving perpendicular to the symmetry axis of the point-plane geometry can be properly imaged. The streamer images shown here are presented as anaglyphs with red and cyan colours for images from the two respective cameras like discussed in [13].…”
Section: Laser Guiding Experimentsmentioning
confidence: 99%